2016
DOI: 10.1097/htr.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Actigraphy With Polysomnography in Traumatic Brain Injury Neurorehabilitation Admissions

Abstract: Actigraphy is a valid proxy for monitoring of sleep in this population across injury severity and common comorbidity groups. However, further research with larger sample sizes to examine concordance in patients with TBI with disorder of consciousness and spasticity is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…17 Moreover, one research team recently showed that actigraphy correlated with polysomnography-measured total sleep time and sleep efficiency among severe TBI inpatients in a rehabilitation setting. 30 Still, results of the present study reflect an indirect measure of sleep and wake, though actigraphy remains the bestsuited method for the long-term assessment of sleepwake cycles within this clinical population.…”
Section: Resultsmentioning
confidence: 71%
“…17 Moreover, one research team recently showed that actigraphy correlated with polysomnography-measured total sleep time and sleep efficiency among severe TBI inpatients in a rehabilitation setting. 30 Still, results of the present study reflect an indirect measure of sleep and wake, though actigraphy remains the bestsuited method for the long-term assessment of sleepwake cycles within this clinical population.…”
Section: Resultsmentioning
confidence: 71%
“…The purpose of this paper was to demonstrate feasibility of data collection, provide programmatic structure for successful implementation, and provide information about the various parameters collected with ACG device used and accompanying proprietary software. Our own work has validated some of the parameters (eg, TST, SE) against electroencephalogram‐based PSG in an acute neurorehabilitation sample [26]. Alternative approaches to scoring the ACG data are possible with this patient population and described in the literature, although the validity of parameters remain uncertain [35].…”
Section: Discussionmentioning
confidence: 98%
“…Our own work with implementation of ACG on an acute brain injury unit has shown it to be feasible and a valid measure of sleep compared with the gold‐standard of PSG [25]. We report moderate‐to‐strong correlations between ACG and PSG for indices such as total sleep time (TST; r = .78, P < .01) and sleep efficiency (SE; r = .66, P < .01) [26].…”
Section: Introductionmentioning
confidence: 87%
“…Actigraphy has shown to be a satisfactory objective estimate of sleep especially for global sleep parameters including total sleep time, sleep onset latency, and sleep efficiency [ 41 ]. Multiple studies have included actigraphy to examine sleep in TBI patients [ 25 , 68 , 69 ], and they have shown that actigraphy is a reliable method for monitoring sleep in this population, irrespective of the injury severity [ 70 ].…”
Section: Methodsmentioning
confidence: 99%